HEALTH STATUS OF ELDERLY A COMMUNITY BASED STUDY - Saxena, Vartika; Kandpal, S D; Goel, Deepak; Bansal, Sushil (Indian Journal of Community Health, 2012)
Background: People at or over the age of 60, constitute above 7.7% of total population. Traditionally this segment of population depends on their children for their health and social welfare, However owing to the social and cultural changes that are taking place within the Indian society, this support may not be as readily available, as it is believed. With the changing demography of India, there is urgent need to look at the health status of elderly for planning appropriate health facilities for them. Objectives: To study biosocial, nutritional and chronic disease risk factor profile of elderly population. Methods: Cross-sectional Study was conducted in Doiwala block of Dehradun district, Uttarakhand. 122 elderly persons of age 60 years and above were interviewed on predesigned questionnaire by house to house visit in the selected village. Results: Overall prevalence of risk factors found to be higher amongst elderly females. Unutrition was higher amongst elderly males. In all, 48.6% elderly were underweight ,10.3% were overweight and 5.6% cases were in obese category. As per the Waist and hip ratio 47.2% elderly belonged to the moderate to high risk category. 30.8% people were hypertensive. Conclusions: Prevalence of high-risk factors for chronic diseases is quite high amongst elderly population, especially amongst elderly females.